Midlife cardiorespiratory fitness and the long-term risk of chronic obstructive pulmonary disease. Issue 9 (17th June 2019) - Hansen, Gorm Mørk; Marott, Jacob Louis; Holtermann, Andreas; Gyntelberg, Finn; Lange, Peter; Jensen, Magnus T
Abstract : Background: Good midlife cardiorespiratory fitness (CRF) may reduce the risk of chronic obstructive pulmonary disease (COPD). Reverse causation may play a role if follow-up time is short. We examined the association between CRF and both incident COPD and COPD mortality in employed men with up to 46 years follow-up, which allowed us to account for reverse causality. Methods: Middle-aged men (n=4730) were recruited in 1970–1971. CRF was determined as VO2 max by ergometer test. Categories of CRF (low, normal, high) were defined as ± 1 Z-score (± 1 SD) above or below the age-adjusted mean. Endpoints were identified through national registers and defined as incident COPD, and death from COPD. Multi-adjusted Cox models and restricted mean survival times (RMST) were performed. Results: Compared with low CRF, the estimated risk of incident COPD was 21% lower in participants with normal CRF (HR 0.79, 95% CI 0.63 to 0.99) and 31 % lower with high CRF (HR 0.69, 95% CI 0.52 to 0.91). Compared with low CRF, the risk of death from COPD was 35% lower in participants with normal CRF (HR 0.65, 95% CI 0.46 to 0.91) and 62% lower in participants with high CRF (HR 0.38, 95% CI 0.23 to 0.61). RMST showed a delay to incident COPD and death from COPD in the magnitude of 1.3–1.8 years in normal and high CRF vs low CRF. Test for reverse causation did not alter the results. Conclusion: In a population of healthy, middle-aged men, higher levels of CRF were associated with a lower long-term risk of incident COPD and death from COPD.